Feminities, masculinities, sexualities: Freud and beyond - Chodorow, Nancy J. (The University Press of Kentucky, 1994)
La psychanalyse peut-elle aller au-delà d'une vision monolithique du genre et de la sexualité normale pour aborder les questions de diversité et de variabilité dans le développement du genre et l'identité de genre ? Ses praticiens et théoriciens peuvent-ils rendre des comptes rendus non pathologisants de la variation de l'orientation sexuelle ? S'appuyant sur une lecture attentive des textes psychanalytiques commençant par Freud et sur sa propre expérience clinique, Chodorow [soutient] que la psychanalyse doit encore démêler la domination masculine de l'hétérosexualité. Elle démontre également le manque de compréhension psychanalytique de l'hétérosexualité et la polarisation problématique des sexualités normales et anormales. Chodorow soutient que la psychanalyse doit prêter attention à la spécificité individuelle et au cadre personnel, culturel et social
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; domination masculine; fem1000; genre; hétérosexisme; hétérosexualité; identités LGBTQIA2+; premier cycle; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

A History of Our Own - Eaklor, Vicki L. (The Lesbian Review of Books, 1994)
Lesbians played a role in all phases of Grove development, albeit that of a minority in number and, usually, in terms of power and recognition. Newton devotes two chapters (of eleven) exclusively to lesbians, and this seems adequately proportional to the lesbian presence in the decades she covers. Importantly, the differences for women between the two eras – 1930s to 1960 and 1960 to 1980 – appear to be determined by class and ethnicity rather than by gender. In the earlier period, says Newton, the gay "girls" or "ladies" (Grovers' terms) "were an elite, privileged group who faced relatively little cultural exclusion or discrimination from their male peers" (204); and, she reminds us, in both eras "whatever problems 'girls' had with 'boys,' physical safety was not one of them" (204). Although they never completely shared in the camp sensibility, and not at all in the public sex of the "Meat Rack," then, Grove lesbians were on an even footing (except in numbers) as long as they were white, Protestant, moneyed, artistic/theatrical, and devoted to the "fun" ethos of the settlement (indeed, "party" meant costumes and drinking, never politics). At the opposite end of New York State from Buffalo is Cherry Grove, a gay community as different from that treated in Boots of Leather as the geography symbolizes. As Esther Newton describes it in Cherry Grove, Fire Island, it could be a typical "all-American" postwar town – dominated by the sensibilities of elite WASP males benefiting from the prosperity of the 1950s and 1960s, and hostile at times to those perceived as outsiders (by race, gender, ethnicity) or interlopers (day-trippers, pretentious Pines neighbors). The crucial exception, of course, is that the elitist WASP men (and some women) who built the town were gay. For these reasons, my reactions divided according to my dual identity. As a historian, I found this book superb in every way: it is an engaging narrative of six decades of the area's development textured with insightful commentary on the larger context of American life and questions regarding how and why Cherry Grove originated and endured. However, the lesbian reader in me, although agreeing that the presentation is wonderful (it is actually more fluid and readable than Boots of Leather), reacted to the sexism, racism, anti-Semitism, and classism that have characterized this community at various stages of its existence, and especially to the community's dismissal of women. As Newton herself summarizes in a passage concerning the "invasion" of the neighboring Pines community, "Whatever the Queen's function – selling tickets to a play or blessing the bathers – she also is the Grove, its key symbol and core representation" (269; italics in the original); and she adds in the accompanying endnote, "The normal processes of Grove action and narration tend to marginalize or even erase women" (345, n.7)
Keywords: discipline; histoire; histoire et politique; personnes lesbiennes; ressource en ligne; sciences humaines; sexualité; thématiques

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Sexualité et séropositivité : représentations sociales de femmes séropositives au virus de l'immunodéficience humaine (VIH) - Mensah, Maria Nengeh (Université du Québec à Montréal, 1994)
Publisher: Montréal : Université du Québec à Montréal, 1994.
Keywords: 1900-1999; 1990-1999; IREF; VIH; discipline; mémoires/thèses; périodes historiques; santé; sciences humaines; sexologie; sexualité; thématiques

The Politics of Inside/Out: Queer Theory, Poststructuralism, and a Sociological Approach to Sexuality - Namaste, Ki (Sociological Theory, 1994)
This paper outlines the main tenets of poststructuralism and considers how they are applied by practitioners of queer theory. Drawing on both Michel Foucault and Jacques Derrida, queer theory explores the ways in which homosexual subjectivity is at once produced and excluded within culture, both inside and outside its borders. This approach is contrasted with more sociological studies of sexuality (labeling theory, social constructionism). Whereas queer theory investigates the relations between heterosexuality and homosexuality, sociologists tend to examine homosexual identities and communities, paradoxically ignoring the social construction of heterosexuality. Poststructuralism can inform a sociological approach to sexuality by emphasizing the generative character of all sexual identities. A sociological study of sexuality which is informed by poststructuralism would examine the exclusions implicit in a heterosexual/homosexual opposition. In this process, bisexual and transgender identities can become viable cultural possibilities, and a broad-based political coalition established. Whereas mainstream sociology focuses on the ways in which homosexuals are outside social norms, and whereas queer theory exploits the ways in which this outside is already inside, this perspective suggests that a critical sexual politics seeks to move beyond an inside/outside model.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; méthodologie; post-structuralisme; premier cycle; queer; sciences humaines; sexualité; soc2014; sociologie; thématiques